MOTIF JUDI ONLINE (REMI POKER) SEBAGAI TUMPUHAN MATA PENCAHARIAN KELUARGA DI KELURAHAN WIYUNG, SURABAYA - firnando, Sandi (Paradigma, 2021)
Abstract Social deviation that is still often found in society is the phenomenon of gambling. Not only is it a hobby of gambling but has become a new profession in the present era. The history of the development of gambling dates back to 2300 BC, the emergence of lottery gambling in ancient China. The gambling profession does not have an income that is certain to be used as a daily livelihood to meet the needs of his family. It can be likened to a family whose life is also at stake. Their welfare depends on uncertain income. The purpose of this study is to identify the background of the research subject who makes online gambling the main profession and to find out the responses of people around the research subject in responding to their profession. The method in this research is a qualitative research using the phenomenological approach of Alfred Schutz's ideas. Alfred Schutz's phenomenology is used to examine the because motive and in order to motive of informants who work as online gamblers. The result of the research is that the online gambling profession appears and can survive because of the historical factor of the player while playing Rummy Poker gambling is said to be profitable, and systematically accessing and playing it is quite easy only requires patience and a strong mentality. The background that influences informants makes online gamblers a profession for their families because the motive comes from the belief in making a more effective living and family background. And in order to motive aims to become an online gambler as a livelihood and meet family needs. Keywords: Online Gamblers, Profession, Motive, Family.